Analisis Sikap Peduli Lingkungan Pada Siswa Kelas VI Sekolah Dasar di Kota Ruteng - Yosef Firman Narut; Mikael Nardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
This study mainly aims to describe and analyze the environmental cares of the 6th class elementary school students in Ruteng. Three attitude components were assessed: cognition, affection, and conation components. A descriptive qualitative research were designed through survey method which involved the 6th grade students as the population from elementary schools in Ruteng. Simple random sampling was employed to determine four elementary schools as samples; those schools were SDK Ruteng 1, SDK Ruteng 3, SDI Wae Ri'i, and SDI Karot. The data were collected through a questionnaire while the data analysis technique was based on Miles and Huberman models which covers reduction, data display, and conclusion / verification. The data were validated in triangulation test, namely: theory triangulation, data triangulation, and expert triangulation. The results of the study showed that the average score of environmental care attitudes of the 6th students’ in Ruteng was 77.81 in a good category. Meanwhile, the average of attitude score components covering the cognition component was 80.3 in the excellent category, affection component was 80.05 in the excellent category, and the conation component was 73.1 in the good category. Based on four elementary school samples, those results were consistently found and the environmental care score on the conation component was lower than the other two components. This indicates that cognitive and affective factors do not necessarily affect on students' conations. Even though the students have awareness (cognition) and feelings (affection) related to the surrounding environmental problems, these are not visible in their daily behavior (conation).